2017
DOI: 10.24326/asphc.2017.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar of the Application Chitosan and Reduced Irrigation on Essential Oil Yield, Total Phenol Content and Antioxidant Activity of Extracts From Green and Purple Basil

Abstract: Phenolic compounds are naturally occurring substances in plants. Basil (Ocimum basilicum L.) belongs to the family Lamiaceae, is a good source of phenolic compounds and natural antioxidants. Elicitors can activate specific genes involved in secondary metabolite biosynthesis. Chitosan, as elicitor, is a natural biopolymer modified from chitin, which is the main structural component of squid pens, cell walls of some fungi and shrimp and crab shells. On the other hand, water deficit stress is one of the most abio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
12
1
1
Order By: Relevance
“…In the present study, indeed, the elicitation of basil and parsley with both treatments reduced the phenylpropanoid content in the EOs of the treated samples. This finding is in contrast with several published studies, where chitosan is reported as an enhancer of the phenylalanine ammonia lyase and of the chavicol-O-methyl transferase enzymes, involved in the phenylpropanoid biosynthesis [ 38 , 39 , 40 ]. The different response of the two species to the elicitation treatments was also evident on the different level of compositional dissimilarity induced in the HS and the EO compositions.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, indeed, the elicitation of basil and parsley with both treatments reduced the phenylpropanoid content in the EOs of the treated samples. This finding is in contrast with several published studies, where chitosan is reported as an enhancer of the phenylalanine ammonia lyase and of the chavicol-O-methyl transferase enzymes, involved in the phenylpropanoid biosynthesis [ 38 , 39 , 40 ]. The different response of the two species to the elicitation treatments was also evident on the different level of compositional dissimilarity induced in the HS and the EO compositions.…”
Section: Discussioncontrasting
confidence: 99%
“…Synthesis of flavonoid and phenolic compounds is initiated very quickly after elicitation. Overall, elicitors like chitosan are involved in some signal transduction systems that induce gene expression of enzymes of the secondary metabolic pathway, such as PAL 46 . A positive correlation was observed between PAL activity and the total content of phenols and flavonoids which shows that chitosan treatment can regulate the accumulation of phenolic compounds through stimulating PAL activity.…”
Section: Resultsmentioning
confidence: 93%
“…Ghasemi Pirbalouti et al (2017) stated that low IC50 indicates a stronger ability of extract to act as a DPPH scavenger, while high IC50 is indicator of a lower ability of scavenging activity and a lot of scavenging is needed to achieve 50% of reaction. Zia et al (2007) stated that the inhibitory effect of DPPH was observed at the highest concentrations in cell cultures treated with salicylic acid and methyl jasmonate (200 μM), in fact the highest antioxidant activity for salicylic acid and methyl jasmonate was at moderate concentrations of 100 µM, therefore, this can be described in terms of inhibitory feedback that occurred in metabolic pathway, it seems that these two elicitors enhance antioxidant levels at lower concentrations and may be due to their positive effects on plant defense signaling.…”
Section: Antioxidant Activitymentioning
confidence: 99%